Macroeconomic variables and Malaysia house price - Aisyah Binti Zulkifli; Mori Kogid; Saizal Pinjaman; James M. Alin (Faculty of Business, Economics and Accountancy, 2021)
Malaysia is one of the developing countries that facing an upward trend in demand for housing. However, the increasing trend in housing prices has become worrying. This study aims to examine the macroeconomic determinants of the housing price in Malaysia. The house price index and macroeconomic data on gross domestic products growth, consumer price index and money supply were collected based on quarterly basis over the period from 2000 to 2019. The Autoregressive Distributed Lag (ARDL) model was used to investigate the effects of long-run and short-run estimates of the proposed econometric model based on the selected macroeconomic variables mention above. The results from the Augmented Dickey-Fuller and Phillips-Perron tests of stationarity indicated that all the variables were non-stationary at the level, I(0) but stationary at the first difference, I(1). The long-run coefficient estimates showed that the gross domestic product and money supply are significant and positively influenced the house price index in Malaysia. In addition, the consumer price index was also significant, but has negative relationship with the house price index in the long run. Further analysis using causality tests revealed that statistically only gross domestic product and money supply were found significant in influencing the house price index in the short-run.